2- and 3-Fluoro-3-deaza-1′, 6′-isoneplanocin: Synthesis and antiviral properties (including Ebola and Marburg). (1st April 2023) - Liu, Chong; Chen, Qi; Schneller, Stewart W.
Graphical abstract: Abstract: To extend the antiviral properties of 2- and 3-fluoro-3-deazaneplanocins into the evolving 3-deaza-1′, 6′-isoneplanocin library, 2- (11 ) and 3-fluoro-1′, 6′- iso -3-deazaneplanocin A (12 ) have been explored. The requisite synthesis began with an Ullmann reaction by coupling of a protected cyclopentenyl iodide with either 2-fluoro- or 3-fluoro-3-deazaadenine. Target 12 displayed significant activity towards 5 viruses (μM): H1N1 (EC50  < 0.36, CC50  > 357, SI > 1000), hepatitis B virus (EC50 1.28, CC50  > 357, SI > 279), norovirus (EC50 0.64, CC50  > 357, SI > 558), Ebola (EC50  < 0.1, CC50  > 100, SI > 1000), and Marburg (EC50  < 0.1, CC50  > 100, SI > 1000). On the other hand, while 11 showed limited antiviral effects, its toxicity was significant, precluding any further usefulness.